Social Values and the Meaning of Barikan Tradition in Sumberejo, Donorojo, Jepara - Muhammad Jodi Prasetiyo; Ainun Wahayuningtiyas; Destina Marta Fiani (JURNAL PENDIDIKAN IPS, 2023)
Tradition is a habit that is passed down from generation to generation and binds the perpetrators. A tradition must be preserved so that later this tradition does not become extinct and can be passed on to the next generation. A tradition indeed contains a special meaning and specific values. As is the case in the barikan tradition, which will be studied in this study. The purpose of this study is to explain directly how the barikan tradition is carried out and to find out the social values and meaning of the barikan tradition in the village of Sumberrejo Donorojo Jepara. This research method uses a descriptive qualitative approach with data sources derived from interviews, observation, and literature studies. The results of this study indicate that the barikan tradition is a tradition held to ask for protection from the almighty so that it is always given health, great fortune and kept away from distress. The barikan tradition is still carried out and preserved to this day. This tradition is carried out at the end of the village or at a T-junction of the town with special foods provided, such as market snacks and manakin chicken and fruit, as a condition for carrying out the barikan tradition, which has its meaning. The positive impact of implementing this tradition can be seen in its social values, namely creating polite, religious, cooperation, caring, togetherness, and kinship attitudes.